The Bovine Hepatic Cell Line BFH12 as a Possible Model for Hepatosteatosis in Dairy Cows - Reichelt, Kristin; Niebisch, Anna M.; Kacza, Johannes; Schoeniger, Axel; Fuhrmann, Herbert (Frontiers in Veterinary Science, 2022)
Hepatosteatosis is a common metabolic disorder of dairy cows, especially during early lactation. Currently, there are a few models of bovine hepatic steatosis available, including primary hepatocytes, liver slices and animal models. Studies which elucidate the influence of single fatty acids on lipid classes, fatty acid pattern, gene expression and phenotypic changes are still limited. Hence, we investigated the suitability of the fetal bovine hepatocyte-derived cell line BFH12 as a model for hepatosteatosis. To create a steatotic environment we treated BFH12 with stearic acid, palmitic acid or oleic acid in non-toxic doses. Thin-layer chromatography and gas chromatography were used to analyze lipid classes and fatty acid pattern, qPCR was used to quantify gene expression of relevant target genes. Lipid droplets were visualized with confocal laser scanning microscopy and evaluated for number and size. Treatment with oleic acid increased triglycerides, as well as lipid droplet count per cell and upregulated carnitine palmitoyl transferase 1, which correlates with findings of in vivo models. Oleic acid was largely incorporated into triglycerides, phospholipids and non-esterified fatty acids. Stearic acid was found mainly in non-esterified fatty acids and triglycerides, whereas palmitic acid was mainly desaturated to palmitoleic acid. All three fatty acids downregulated stearyl-CoA-desaturase 1. In conclusion BFH12 can acquire a steatotic phenotype by incorporating and accumulating fatty acids. Oleic acid is particularly suitable to produce hepatosteatosis. Therefore, BFH12 may be a useful in vitro model to study bovine hepatosteatosis and its underlying molecular mechanisms.